Perlindungan Konsumen Terhadap Produk Makanan Kemasan Usaha Mikro, Kecil, dan Menengah (UMKM) yang Tidak Bersertifikasi Halal di Kota Jambi - Evalina Alissa; Faizah Bafadhal; Diana Amir (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Halal certificati for food and beverage products is highly important, especially for Muslim consumers, in order to provide convenience options. Law No.33 of 2014 Concerning Halal Product Guarantees (UUJPH) has clearly regulated that every imported, distributed, and available products in the Indonesian market are required to be halal-certified. This study specifically aims to: 1) Analyze consumer protection toward packaged food products of Micro, Small and Medium Enterprises (MSMEs) that are not halal-certified in Jambi City, 2) Analyze the limitations toward the halal- certified packaged food products of MSME players in Jambi City, 3) Analyze government supervision toward the packaged food products of MSME players in Jambi City. This study is using a Juridical Empirical method, and the specifications are descriptive. The result shows: Consumer protection for packaged food products of MSMEs that are not halal certified in Jambi City has not been optimally provided. This is due to many enterprise hasn't register the product yet to get halal certification on Halal Office of Jambi Province. 2. Limitations to the MSME players of packaged food products that are not halal-certified in Jambi City includes: 1) lack of understanding among business players regarding halal certification, 2) incomplete documents, 3) business products are not fully developed/unstable, 4) expensive costs, 5) yet to renew the halal certification and 6) do not have time to register halal certification. 3. Government supervision on the packaged food products that are not halal-certified in Jambi City is in fact the duty of BPJPH. In fact, the supervision is not in accordance with the current regulation, therefore, it is necessary to partner with other institutions, such as Indonesian Ulema Council (MUI), Indonesian Food and Drug Authority (BPOM), Health Department, Animal Husbandry Service and the whole population.